Production of antibacterial biobased blends for biomedical use - Dervişcemaloğlu, Mete (Graduate School, 2023)
Nowadays, it is getting harder and harder to meet the medical needs of the rapidly increasing world population. The recent global epidemic crisis has once again revealed that it is difficult to meet this need with traditional methods. For this reason, studies on the research of new drug systems and drugs have gained popularity today. Drug delivery systems are carrier systems that prevent the active substance used in the treatment of disease from being degraded by the body while being delivered to the target tissue, and enable the active substance to affect the target tissue instead of the whole body. The drug delivery systems produced today generally deliver the active ingredients to the target area through the digestive tract, injection and implantation. It has been demonstrated in scientific studies that drugs taken by these methods affect healthy organs, cells and natural microflora, as well as diseased organs, cells and pathogens. In addition, the disadvantages such as rapid drug release and rapid removal from the body in traditional drug systems models reduce the efficiency of the active substance used and cause multiple dosing. This, in addition to the increase of the mentioned negative effects caused by the active substance, brings with it increased drug resistance in bacteria that researchers frequently mention.Increasing drug resistance in bacteria reduces the effectiveness of antibiotic use and poses a serious threat to human health. However, the natural antibiotic properties of herbal active substances can be quite effective in fighting these resistant bacteria. Herbal treatments, especially against antibiotic-resistant bacteria, may be more effective in the long run. In addition, the side effects of plant-derived active substances are less than antibiotics and offer the opportunity to treat the body without harming it. Electrospinning is a method in which fibrous active substance carriers are produced at nanoscale with the help of electrical forces from a polymer or polymer mixtures. This method stands out due to its advantages such as high surface-to-volume ratio, diversity in polymeric and active materials that can be combined, easy workability, reasonable cost, and high efficiency production in a short time. Curcumin and oleuropein are natural compounds found in plant sources and are particularly known for their antioxidant properties. Curcumin is a compound found in the turmeric plant and has anti-inflammatory and antioxidant properties. Studies have shown that curcumin can be beneficial in the treatment of a variety of diseases, including cancer, Alzheimer's disease, depression, diabetes, and heart disease. Oleuropein is a compound found in olive leaves and olive oil. Besides its anti inflammatory and antioxidant properties, it has a variety of health benefits such as lowering blood pressure, reducing the risk of heart disease and anti-cancer effects. In this study, it was aimed to produce bio-based drug-loaded antibacterial blends for use in medical conditions such as skin injuries. The limited number of studies in the literature on the use of curcumin and oleuropein with nanocarriers for medical purposes increases the scientific importance of the study. In order to increase the treatment efficiency of the produced transport system, natural and bio-based synthetic polymers were used together. The fact that there is no information in the literature about the poly(ω-pentadecalactone-co-δ-valerolactone) copolymer synthesized by the enzymatic polymerization method has added to the originality of the study. The synthesized hydrophobic and biocompatible copolymer was used to make the polymer drug delivery system resistant to uncontrolled water intake. Gelatin, on the other hand, was blended with the copolymer synthesized for use in electrospinning in order to increase the biocompatibility and hydrophilic character of nanofiber drug-loaded membranes. In this study, Candida antarctica B lipase was immobilized to rice husk ash, on which surface modifications were applied using the immobilization methods used in previous studies, primarily to be used in enzymatic polymerization reactions. ω pentadecalactone-co-δ-valerolactone copolymer was produced by ring-opening polymerization using immobilized enzyme from ω-pentadecalactone and δ valerolactone at different reaction times and temperatures, using monomer ratios of 75-25%, 50-50%, 25-75%. Monomer conversion ratios of the produced copolymers were determined by proton nuclear magnetic resonance spectroscopy (1H-NMR), and molecular weights were determined by gel permeation chromatography (GPC). Based on the advantages of molecular weight in drug delivery systems in the literature, the sample with the highest molecular weight was selected and analyzed in order to determine its thermal properties by using thermal gravimetric analysis and differential scanning calorimetry methods. Water contact angle measurement was analyzed to examine its hydrolytic properties. From the results obtained, it was concluded that an alternative ω-pentadecalactone-co-δ-valerolactone copolymer was synthesized to the ω-pentadecalactone-co-ε-caprolactone copolymer synthesized in previous studies and could be used in medical studies. In the second stage of the study, a blend of the highest molecular weight copolymer and gelatin natural polymer produced for use in the electrospinning process was obtained. While forming the copolymer and gelatin blend, 1,1,1,3,3,3- Hexafluoroisopropanol, which was used in previous studies, was used as the solvent. The blend was prepared with 15% copolymer and 8% gelatin by weight. Nanofiber membrane was produced from the produced blend by electrospinning process at a flow rate of 2 ml/hour, under 23-28 kV. Scanning electron microscopy was used to examine the nanofiber morphologies of the produced membrane. Since no bead-like structure was observed in the nanofibers produced in the images, it was seen that the electrospinning process was successful and smooth nanofibers were produced. The average diameter of the nanofibers was measured as 546.1±193.1 nm. In order to increase the durability of the produced nanofiber membranes in the aqueous environment, a 2-hour cross-linking process was applied in glutaraldehyde vapor as applied in previous studies. Afterwards, the membranes were immersed in a pH 7.4 phosphate buffer solution and their in vitro degradation properties were investigated. Cross-linked samples immersed in phosphate buffer were placed in a shaking water bath. Cumulative weight loss was calculated at 7 , 14 , 21 , 28 days intervals. At the end of the 28th day, the cumulative weight loss percentage in the cross-linked membrane was calculated as 22.9% and the cumulative weight loss percentage in the non-crosslinked membrane was 92.8%, it was concluded that the cross-linking process increased the durability of the membranes in the aqueous environment. The characterizations of the produced copolymer/gelatin nanofiber membranes and the copolymer/gelatin nanofiber membranes after the crosslinking process were made by thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), water contact angle measurement. As a result of the water contact measurement, it was observed that the gelatin of the nanofiber membrane obtained from the hydrophobic copolymer and gelatin blend was hydrophilic, and the hydrolytic resistance increased after cross-linking. In the DSC results, the melting enthalpy decreased due to the changed crystallinity caused by the gelatin added to the blend. On the other hand, the melting enthalpy of the cross-linked nanofiber copolymer/gelatin membrane increased compared to the non-crosslinked nanofiber copolymer/gelatin membrane. From these results, it was concluded that the crosslinking process increased the thermal endurance of the nanofiber membrane. TGA results also support this assessment. According to all these characterization analyzes, it was observed that crosslinking increased the hydrolytic and thermal resistance of the copolymer/gelatin nanofiber membrane and the crosslinking resulted successfully. Finally, SEM images were examined in order to evaluate the morphology of the produced nanofibers, and it was concluded that the synthesized copolymer and gelatin were mixed properly by dispersing throughout the whole structure and smooth fibers were produced. In addition to these, the release studies of the produced curcumin membranes were arranged. Using the Box-Behnken method, release experiments with pH, temperature, concentration factors were designed and the effects of these factors on cumulative release were investigated by deducing the reaction surface methodology. Release studies were carried out at 5%, 15% and 25% curcumin concentrations at pH=5.5, 7.0, 8.5 and 33,35,37 °C parameters, corresponding to the normal, wound inflammation and subsequent pH-temperature values of the skin. As a result of the correlation coefficients (R 2 ) comparison of the obtained and estimated results, and the designed release experiments were found to be statistically appropriate. While examining the release kinetics, non-linear regression was applied and it was observed that the two mathematical models (Higuchi and Korsmeyer-Peppas) best fit and non-Fickian type diffusion occurred in the nanofibers. The fact that the best cumulative curcumin release was found in normal skin and inflamed wound parameters, at 25% curcumin concentration, showed that the produced curcumin-loaded nanofiber membranes could be used with high efficiency in the protection of skin health and wound treatment. As a result, it has been proven that gelatinous curcumin/oleuropein loaded membranes obtained from enzymatically synthesized copolymer can be used in the protection of skin health due to their antibacterial properties. It has been demonstrated that curcumin-loaded copolymer/gelatin nanofibers can be used to promote cell proliferation in the treatment of wound inflammations as well as maintaining skin health. It is thought that the use of oleuropein in different nanocarriers such as nanofibers may support the durability and thermal properties of the structure in aqueous media.
Biyomedikal alanlarda kullanılmak üzere antibakteriyel özellikli biyobazlı harmanların eldesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: biotechnology; biyoteknoloji; biomedical materials; biyomedikal malzemeler